Konsep Dasar Evaluasi Pembelajaran di SDN Karang Tengah 10 - Magdalena, Ina; Juliasih, Juliasih; Maulida, Luthfia Nur; Andriliani, Luthfiah (YASIN, 2023)
This study aims to examine the evaluation of the learning process at the elementary school level. An effective learning process can improve the quality of education. However, evaluation is often ignored by educators, who focus on implementing learning only. Improper assessment and falsifying value evaluations can have a negative impact on learners and the overall quality of education. Therefore, this study uses a qualitative approach and literature study methods. Data were collected from various literature sources related to learning evaluation at the elementary school level. Data analysis was performed using content analysis techniques to hide information, provide explanations, and draw conclusions. The results of the study show that evaluation plays an important role in obtaining valid data about students' abilities. The data becomes the basis for making decisions related to learning and assessing the quality of teaching. Creativity and high motivation from educators are needed to create an interesting learning process for students.